Check sibling questions

Ex 9.4, 3 (vi) - Simplify (x + y)(x^2 - xy + y^2) - Chapter 9 Class 8

Introducing your new favourite teacher - Teachoo Black, at only ₹83 per month


Transcript

Ex 9.4, 3 Simplify. (vi) (𝑥+𝑦)(𝑥^2−𝑥𝑦+𝑦^2 ) (𝑥+𝑦)(𝑥^2−𝑥𝑦+𝑦^2 ) = 𝑥(𝑥^2−𝑥𝑦+𝑦^2 )+𝑦(𝑥^2−𝑥𝑦+𝑦^2 ) = (𝑥×𝑥^2 )−(𝑥×𝑥𝑦)+(𝑥×𝑦^2 )+(𝑦×𝑥^2 )−(𝑦×𝑥𝑦)+(𝑦×𝑦^2 ) = 𝑥^3−𝑥^2 𝑦+𝑥𝑦^2+𝑦𝑥^2−𝑥𝑦^2+𝑦^3 = 𝑥^3−𝑥^2 𝑦+𝑥^2 𝑦+𝑥𝑦^2−𝑥𝑦^2+𝑦^3 = 𝑥^3−𝑥^2 𝑦+𝑥^2 𝑦+𝑦^3 = 𝒙^𝟑+𝒚^𝟑 (𝑦𝑥^2=𝑥^2 𝑦)

Davneet Singh's photo - Teacher, Engineer, Marketer

Made by

Davneet Singh

Davneet Singh is a graduate from Indian Institute of Technology, Kanpur. He has been teaching from the past 12 years. He provides courses for Maths and Science at Teachoo.